Revenue Administration : Taxpayer Audit--Development of Effective Plans. (Technical Notes and Manuals; Technical Notes and Manuals ;, 2010)
This technical note describes how to develop effective plans for a taxpayer audit. The note highlights that a well-managed audit program plays a major role in managing compliance. An effective audit program will have significantly wider impacts than just raising revenue directly from audit activities. The note discusses that a well-planned audit program can provide the administration with significant leverage across the community. The note also describes the value of audit planning, and the methodology for developing an audit strategic plan.